Investigating the scale of herding in Chalcolithic pastoral communities settled along the Danube River in the 5th millennium BC: A case study at Borduşani-Popină and Hârşova-tell (Romania). (2nd May 2017) - Balasse, Marie; Bălăşescu, Adrian; Tornero, Carlos; Fremondeau, Delphine; Hovsepyan, Roman; Gillis, Rosalind; Popovici, Dragomir
Abstract: In southeastern Romania, the Gumelniţa culture is characterized by the appearance of tell sites. Whether this phenomenon was accompanied by increasing specialization of the economy may be investigated through the zooarchaeology of pastoral systems. The scale of herding is an important element of this framework. A case study was conducted on the tell sites of Hârşova and Borduşani-Popină situated in the Danube River basin. Both sites, located respectively on a terrace of the river and on the island of Balta Ialomiţei, delivered occupations from the Gumelniţa A2 dated to the second half of 5th millennium cal BC. Their occupants subsisted on an economy focused to a large extent on aquatic resources but also heavily dependent on cattle, pig and caprines husbandry and agriculture. The role of riverbanks resources in herding strategies and the extent to which the island of Balta Ialomiţei may have sustained domestic animal stocks was addressed through stable isotope analysis of animal skeleton remains. At both sites, results revealed local herding for cattle and caprines, reflected in an unexpectedly high contribution of C4 plants to their diet, most likely from ruderal C4 plants that are more abundant around the settlements as well as in cultivated fields. Domestic pigs had a higher trophic status than their wild counterparts, highlighting a significant contribution of animal protein to their diet most likely provided by human activities, suggesting that they were maintained in the settlement. Overall the findings suggest domestic stocks were reared in close proximity to the settlements, rather than in an extensive system. This scheme complements the small-scale cultivation system highlighted from the archaeobotanical analysis. Gumelniţa tell sites have been previously described as being part of larger pastoral systems including locations with complementary functions, although functional complementarity in time was not made explicit in this model. In this regard, the results obtained at Hârşova and Borduşani-Popină are not in favour of large-scale seasonal mobility.